Using glucagon-Like Peptide-1 Agonists for Post-Bariatric Surgery: A Narrative Review - Oshidari, Bahador; Soori, Mohsen (Novelty in Biomedicine, 2026)
Background: Post-bariatric surgery weight regain, or lack of optimal weight loss, are two common problems after bariatric surgery. Some studies recommend the administration of glucagon-like peptide-1 (GLP-1) agonists for weight loss in these conditions. In this study, we aimed to review prior studies evaluating the effects of GLP-1 after bariatric surgery. Materials and Methods: In this narrative review, we reviewed studies from 2015 to 2025 using the keywords “bariatric surgery,” “GLP1,” “Glucagon-like peptide-1,” “sleeve gastrectomy,” “Roux-en-Y,” and “Gastric Bypass.” Keywords were searched in PubMed/MEDLINE, Web of Science, EMBASE/Elsevier, Scopus, and CENTRAL. After considering the exclusion criteria, ten studies were enrolled in the review. Results: GLP1 agonists significantly reduced weight in patients who did not experience weight loss as expected and in patients who experienced weight regain. Different types of GLP1 agonists had different effectiveness; in this respect, semaglutide had better effects than Liraglutide. Side effects of GLP1 agonists were tolerable and primarily gastrointestinal. Conclusion: GLP1 agonists are safe and effective therapies for weight regain or suboptimal weight loss after bariatric surgery.